Bioactivity studies of Huh-7 cells derived human epidermal growth factor expressed in Pichia pastoris. Issue 6 (3rd June 2017) - Khan, Mohsin Ahmad; Ahmed, Nadeem; Khan, Muhammad Islam; Zafar, Ahmad Usman; Tahir, Saad; Anjum, Muhammad Sohail; Ali, Muhammad; Khan, Faidad; Husnain, Tayyab
Abstract: Previously, we have reported cloning of human epidermal growth factor gene from Huh - 7 cells and its extracellular expression in Pichia pastoris . The presented work is a detailed report regarding molecular characterization of Huh - 7 cells-derived hEGF expressed in Pichia pastoris with special reference to its glycosylation profiling and bioactivity studies. Densitometric scanning of SDS-PAGE separated extracellular proteins from hEGF recombinant Pichia pastoris strain indicated that about 84% of the extracellular proteins were glycosylated. Size exclusion chromatography using Superdex 75 prep grade column was successfully utilized to separate fractions containing glycosylated and non-glycosylated extracellular proteins. In dot blot assay, hEGF was detected in both glycosylated and non-glycosylated fractions. Bioactivity assays revealed that both glycosylated and non-glycosylated fractions were bioactive as determined by cell viability assay. It was also observed that hEGF present in non-glycosylated fraction was relatively more bioactive than hEGF present in glycosylated fraction. Graphical abstract: : Bioactivity studies of Huh-7 cells-derived human epidermal growth factor expressed in Pichia pastoris .